The Impact of The Utilization of Electronic Payment Moderated by Financial Technology Innovation on Financial Technology Payment in Indonesia - Surjadi, Julisar; Supriatna, Dicky; Debora, Debora (Jurnal Sistem Informasi Bisnis, 2025)
Information technology is currently developing rapidly and covers many aspects of people's lives. The development of information technology also includes in the financial sector. The development of information technology in the financial sector is referred to as Financial Technology. The purpose of this study was to test and analyze The Utilization of Electronic Payment moderated by Financial Technology Innovation on Financial Technology Payment in Indonesia. The theories used in this study are the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), Electronic Payment, Financial Technology, Diffusion of Innovation Theory, and Financial Technology Payment. Diffusion of Innovation (DOI) Theory in 1962, making it one of the earliest social science theories. A theory known as "diffusion of innovations" aims to explain how, why, and how quickly new concepts and technologies proliferate. Everett Rogers made the theory more widely known in his 1962 book Diffusion of Innovations. The research method used in this research is quantitative methods with primary data obtained from distributing questionnaires using Google Form. The data were collected from 316 respondents. The questionnaire was structured using a Likert Scale of 1-5 (Strongly Disagree - Strongly Agree). The research data were analyzed using the Structural Equation Model (SEM) with WarpPLS7. The results showed that The Utilization of Electonic Payment accepted with P Value < 0.01 to Financial Technology Payment in Indonesia. The Information Technology Innovation variable can act as a moderating variable between The Utilization Electronic Payment and Financial Technology Payment  in Indonesia with P Value = 0.01